High photocatalytic activity of Ag/Ag3PO4:W heterostructure formed by femtosecond laser irradiation - Trench, Aline Barrios; Teodoro, Vinícius; da Trindade, Letícia Guerreiro; Machado, Thales Rafael; Minguez-Vega, Gladys; Cordoncillo, Eloisa; Doñate-Buendía, Carlos; Andrés, Juan; Longo, Elson (Eclética Química, 2022)
In this work, the W-doped Ag3PO4 was prepared by the chemical coprecipitation method and irradiated with a femtosecond laser (FL). The successful formation of the Ag/Ag3PO4:W heterostructure was confirmed by XRD analysis. A higher structural disorder in the [PO4] clusters was observed for the FL irradiated sample (Ag3PO4:W-FL), indicating the formation of Ag metallic from the Ag3PO4 structure. The photocatalytic activity of the samples was studied by photodegradation of rhodamine B under visible light irradiation. The formation of Ag nanoparticles on the surface of Ag3PO4:W led to a degradation rate constant 3.54 times higher than the nonirradiated sample. This higher photocatalytic activity was related to the surface plasmon resonance effect of the Ag metallic, which acts by capturing photoexcited electrons from the Ag3PO4:W, avoiding the recombination of electron-hole pairs, and thus improving the photocatalytic activity.